AN ATTEMPT OF LANDSCAPE-ECOLOGICAL ZONATION OF SYUNIK MARZ TERRITORY (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
A detailed analysis of natural and anthropogenic elements of Syunik Marz territory, standardization of respective score values, selection of expert weight factors and subsequent collation of those factors enabled us to produce a map of landscape-ecological pressure. Treating the map as a base we provided landscape-ecological zonation of Syunik Marz territory and finally defined 3 landscape-ecological regions and 17 sub-regions.
Keywords: Syunik Marz; landscape-ecological pressure; landscape-ecological zonation